2002
DOI: 10.1128/mcb.22.19.6820-6830.2002
|View full text |Cite
|
Sign up to set email alerts
|

Gene Structure and Functional Analysis of the Mouse Nidogen-2 Gene: Nidogen-2 Is Not Essential for Basement Membrane Formation in Mice

Abstract: Nidogens are highly conserved proteins in vertebrates and invertebrates and are found in almost all basement membranes. According to the classical hypothesis of basement membrane organization, nidogens connect the laminin and collagen IV networks, so stabilizing the basement membrane, and integrate other proteins. In mammals two nidogen proteins, nidogen-1 and nidogen-2, have been discovered. Nidogen-2 is typically enriched in endothelial basement membranes, whereas nidogen-1 shows broader localization in most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
125
1
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(133 citation statements)
references
References 61 publications
(103 reference statements)
4
125
1
3
Order By: Relevance
“…The ability of laminin to form gel-like aggregates in vitro in the presence of calcium ions (Yurchenco and Cheng, 1993) suggests that minimal matrices, containing laminins as major structural components, are sufficiently stable to form laminar structures and enable differentiation, proliferation and survival of cells. The hypothesis that only laminins are crucial during early development is supported by the fact that the deletion of the laminin γ1 chain caused fatal consequences during the periimplantation period (Smyth et al, 1999), but not the ablation of any other basement membrane component analyzed so far (Costell et al, 1999;Murshed et al, 2000;Schymeinsky et al, 2002). However, there is currently no ultimate model available to describe the molecular organization of basement membrane components in early embryos.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability of laminin to form gel-like aggregates in vitro in the presence of calcium ions (Yurchenco and Cheng, 1993) suggests that minimal matrices, containing laminins as major structural components, are sufficiently stable to form laminar structures and enable differentiation, proliferation and survival of cells. The hypothesis that only laminins are crucial during early development is supported by the fact that the deletion of the laminin γ1 chain caused fatal consequences during the periimplantation period (Smyth et al, 1999), but not the ablation of any other basement membrane component analyzed so far (Costell et al, 1999;Murshed et al, 2000;Schymeinsky et al, 2002). However, there is currently no ultimate model available to describe the molecular organization of basement membrane components in early embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Laminins are a family of at least 15 distinct heterotrimeric molecules, which form gel-like aggregates (Colognato and Yurchenco, 2000). Nidogen-1 and -2 mediate the formation of ternary complexes between laminin and collagen IV in vitro (Fox et al, 1991;Kohfeldt et al, 1998), but their significance in vivo is not yet fully defined (Murshed et al, 2000;Schymeinsky et al, 2002). Heparan sulfate proteoglycan perlecan is integrated into the networks of laminins and collagen IV and plays important roles in the maintenance of basement membrane integrity, its filtration functions and also the local storage of growth factors .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nidogen is constitutively located in areas of epithelial-mesenchymal interactions where it is secreted by the resident fibroblasts (Fox et al, 1991;Marinkovich et al, 1993;Ekblom et al, 1994), which has been confirmed in experimental systems in vitro (Fleischmajer et al, 1995;Smola et al, 1998). In mammals two isoforms have been discovered, nidogen-1 which is the major form, and nidogen-2 (Kohfeldt et al, 1998), and knockout mice have been generated (Murshed et al, 2000;Dong et al, 2002;Schymeinsky et al, 2002) providing a more specific functional proof. The complete lack of either nidogen-1 or -2 did not produce an obvious phenotype in basement membrane structures or related functions.…”
Section: Introductionmentioning
confidence: 95%
“…Mice that lack expression of either nidogen 1 or nidogen 2 have normal life spans and are relatively healthy and fertile (Murshed et al, 2000;Schymeinsky et al, 2002). Functional basement membranes are also deposited during early embryogenesis in nidogen 1 and 2 double-knockout mice, suggesting that other matrix components compensate for the lack of both nidogens, or that there is direct binding of laminin to type IV collagen that can bypass nidogens (Bader et al, 2005).…”
Section: Nidogensmentioning
confidence: 99%